Shape-memory and self-healing properties of sustainable cellulosic nanofibers-based hybrid materials for novel applications - Muhammad Yasir Khalid; Zia Ullah Arif; Ans Al Rashid; Syed Muhammad Zubair Shah Bukhari; Mokarram Hossain; Muammer Koç (Giant, 2024)
In the era of smart and sustainable technology driven by naturally occurring materials, various nanocellulose-based materials play a crucial role. Shape memory behaviour and self-healing capabilities of nanocelluloses are emerging as focal points in numerous research domains. Nanocellulose and its derivatives such as cellulose nanocrystals (CNC) and cellulose nanofibers (CNF), are currently in the limelight due to their excellent shape-memory and self-healing properties, making them suitable for multifunctional devices. In this regard, CNF, as a cutting-edge material, has spurred researchers to explore its potential in developing contemporary multifunctional and personalized health devices. Therefore, a timely and comprehensive review is essential to gain deep insights into the effectiveness of shape-memory and self-healing capabilities of CNF for multifunctional devices. Herein, we first provide a brief introduction to all nanocellulose materials. This review also depicts recent advancements and breakthroughs in the large and effective synthesis of CNF-based hybrid materials. Next, focusing on their self-healing and shape-memory performance, this review sheds new light on the advanced applications of CNF materials. Finally, perspectives on the current challenges and opportunities in this field are summarized for future researchers to gain an in-depth understanding of CNF-based smart and sustainable materials.